Do estatuto do servidor público à terceirização em Erechim : o trabalhador em busca de seus direitos (2010-2011) - Pavan, Domingos Roque (2017)
The outsourcingit is the administrative technique to transfer to others some services that were previously done internally by companies and institutions. Following this trend, outsourcing has also been introduced in public administration. It is about this issue that this search talks about. Outsourcing services in the public service and the reflexes arising from this relationship relative to civil servants, passing by the weakening of the statute that rules the public career. Therefore it is made a contextualization with the historical perspective of the Brazilian Public Administration, taking as starting point the arrival of the Portuguese royal family to Brazil, because we believe it was from that moment on that the country began to have an administrative autonomy, even if this autonomy was managed by Portuguese people. Following the historical order we pass by other governments, highlighting in each one of them relevant administrative events that, somehow, prepared the way for outsourcing to be a reality nowadays. In this perspective, the administrative events from the 1980s have greater relevance because it is from there that the state reform project was intensified, opening the doors of Public Administration for outsourcing. This opening collides directly with the interests of public servants who see their autonomy affected and understand that it generates precarious working conditions. The study discusses the various sides of outsourcing, showing the arguments of those who defend and also those who criticize this new way of hiring. This research is Links to social history of work. In this perspective, are used as a source, court cases found in Labor Justice of Erechim which were received in 2010 and 2011 and have as part the outsourced service companies, contracted by Erechim's Town Hall, and its employees. By means of the analysis of the processes we tried to draw a profile of who are the outsourced workers and know what rights these workers need to seek in court to be recognized.